Te wā o naianei : an exhibition report presented in partial fulfilment of the requirements for the degree of Masters in Māori Visual Arts, Massey University, Palmerston North, New Zealand - Munn, Justine (Massey University, 2024)
The exhibition report begins with a brief historical focus upon the representation of Māori in paintings by late 18th-century european artists. It examines two artists that utilised classical techniques in their portrayals of tūpuna Māori, whilst one artist paints a dramatic image in romanticism. In addition, I include my own connection to a tupuna through classical portraiture. The literature review highlights contemporary wāhine Māori painters who have implemented painting techniques in portraiture and figurative art within the paradigm of customary Māori visual storytelling, moving beyond colonial documentation. These modern works engage with themes such as kōrero, pūrakau, atua Māori, Rangatahi and the impact of the urban shift moving from their ancestral tūrangawaewae, and whānaungātanga. In further their art contextualises the social and political issues of Māori history and contemporary challenges from colonisation in Aotearoa. The report then leads into the discussion of the methodology for the main body of work, concentrating on how whānaungātanga and whānau are expressed through portraiture and figurative imagery. My works pay tribute to my parents, impacted by the rural migration for work and training, whilst maintaining their turangawaewae. Furthermore, the exhibition aligns with the kaupapa Māori research principles and the strategic commitment to upholding the principles of Te Tiriti o Waitangi, of Nga Toi Māori, Taonga Gallery and Studios gallery, Okorere.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts); 360602 Fine arts